AND/OR graph generation for disassembly analysis: Deeply-nested subassemblies represented by a hypergraph - Iwase, S. (International journal of production research, 2025)
Manufacturers are demonstrating increased responsibility towards the environmental performance of their products throughout their life-cycles to promote a sustainable society and attain the sustainable development goal of being 'responsible consumption and production'. Designers need to pivot from production-oriented to environmental-protection designs, prioritising reusability and recyclability from the onset of the design process. Consequently, a design for disassembly (DfD) strategy has been developed. This study proposes a method to construct a disassembly model for a complex product using a hypergraph representing its subassemblies as hyperedges. Hypergraphs can represent deeply-nested subassembly structures in a single matrix, and the disassembly precedence relationships can be easily determined using a 'cut-set' matrix newly defined in this study from the incidence matrices of the graph and hypergraph. Designers can easily modify subassembly elements by changing the hyperedge and building disassembly models for various cases. The disassembly model is represented as an AND/OR graph, and the effectiveness of this algorithm is demonstrated in two realistic case studies. The proposed approach will facilitate integrating reusability and recyclability into products, which will help address global warming and carbon neutrality.